Chemical scarification unlocking cashew nut germination potential: Enhancing cashew seed germination through chemical scarification - Rahman, M S; Sarker, P C; Jahan, T; Akter, S E; Mahmud, S A; Reza, M S (Bangladesh Journal of Agriculture, 2026)
The Seed Technology Division of BARI, Gazipur carried out a lab test to identify the best chemical scarification agent for improving germination and seedling performance of cashew nut. Water and vinegar at 25% and 50% concentrations were used as chemical scarification means. The seeds were soaked into `water and vinegars for 0, 24, 48, 72, and 96 hours following completely randomized design (CRD) with three replications. . The results of the study reveal that germination percentage of cashew nut went up due to priming over varying times. Among the treatments, soaking cashew nut seeds in water for 72 hours was found as the most effective method for enhancing seed germination. Bangladesh J. Agri. 2025, 50(2): 30-37